1990. Reactivity and Specificity of a Research Use Only (RUO) Prototype of a Highly Multiplexed Sample-to-Answer PCR System for the Detection of Pathogens from Positive Blood Culture. (26th November 2018) - Antosch, Jeremiah; Spaulding, Usha; Stone, Jessica; Later, Cameron; Koch, Kerrin; Kavetska, Iryna; Ton, Han; Alberti-Segui, Christine; Grange, Anne; Dubost, Caroline; Rogatcheva, Margarita
Abstract: Background: Rapid diagnosis of causative agents of bloodstream infections improves patient outcomes and antibiotic stewardship. BioFire Diagnostics, LLC, is developing the BioFire® Blood Culture Identification 2 (BCID2) Panel, increasing the coverage of the BioFire® FilmArray® Blood Culture Identification (BCID) Panel for key pathogens and antimicrobial resistance (AMR) markers in aerobic and anaerobic positive blood culture (PBC). This revision expands the menu from 27 to 42 targets, with 26 bacterial (14 revised, six new) and seven fungal analytes (two revised, three new), as well as nine AMR markers (one revised, six new). Notable additions include the anaerobe Bacteroides fragilis, the emerging fungus Candida auris, and the mobile colistin resistance gene, mcr -1. This study details the reactivity and specificity of an RUO BioFire BCID2 panel. Methods: The prototype was tested with fungal and bacterial isolates, some carrying AMR markers, at two sites by multiple operators. Reactivity was assessed at 10 6 CFU/mL for 301 analytes, and specificity at 10 8 CFU/mL for 43 on-panel and 93 off-panel strains. Evaluation included multiple strains for species level and AMR marker assays, as well as multiple species for family/genus level assays. Concordance with standard of care (SoC) results was examined for 126 archived PBC. Results: Testing against 136 on-panel organisms, phylogenetic-neighbors, and normal cutaneous flora, showed 100% specificity for 41/42 targets. Reactivity was confirmed for 346/351 target analytes, and comprehensive detection was observed for the revised family-level Enteric assay (90/90) and genus-level Staphylococcus spp. (51/51), Streptococcus spp. (17/17), and Candida spp. (67/71) assays. The prototype showed excellent sensitivity (97.1%) and specificity (99.7%) compared with SoC with archived PBC. Conclusion: Performance of this RUO BioFire BCID2 Panel indicates that many key pathogens implicated in bloodstream infections can be identified with high sensitivity and specificity, and highlights the utility of the expanded menu to provide actionable information. Future panel versions will address observed deficiencies. RUO products used in this study have not been evaluated by the FDA or other regulatory agencies for In Vitro Diagnostic use. Disclosures: J. Antosch, BioFire Diagnostics, LLC: Employee, Salary. U. Spaulding, BioFire Diagnostics, LLC: Employee, Salary. J. Stone, BioFire Diagnostics, LLC: Employee, Salary. C. Later, BioFire Diagnostics, LLC: Employee, Salary. K. Koch, BioFire Diagnostics, LLC: Employee, Salary. I. Kavetska, BioFire Diagnostics, LLC: Employee, Salary. H. Ton, BioFire Diagnostics, LLC: Employee, Salary. C. Alberti-Segui, bioMérieux: Employee, Salary. A. Grange, bioMereiux, Inc.: Employee, Salary. C. Dubost, bioMérieux: Employee, Salary. M. Rogatcheva, BioFire: Employee, Salary.